Bodyweight exercises can acutely impair self-paced interval running performance in male and female runners - Lucas Dalla Vecchia Lanzarini; Poliana Junkes Schmitt; Vinicius Burtet Goulart; Gabriel Macedo Oliveira; Tainara Huff; Thiago Pereira Ventura; Tiago Turnes (Sport Sciences for Health, 2026)
Abstract Concurrent training is frequently utilized by endurance runners due to its physiological and neuromuscular benefits. However, despite its practical relevance, the acute effects of a bodyweight (BW) circuit session on self-paced interval training (IT SP ), in which runners freely regulate their running speed during each interval, and whether these effects differ by sex, remain unclear. Therefore, this study aimed to investigate the acute effects of BW circuit on IT SP performance, perceptual, and physiological responses, comparing male and female runners. Sixteen runners (8 men, 8 women) completed two IT SP sessions (8 × 200 m with 90 s recovery) under randomized, counterbalanced conditions: (i) a control condition and (ii) a condition preceded by a BW circuit consisting of four exercises performed for three sets of 15 s of work and of 45 s rest. Readiness for exercise was evaluated immediately pre IT SP by a 10-point scale. The BW circuit impaired performance (339.9 ± 51.2 vs. 325.1 ± 52.1 s, p < 0.01), irrespective of sex ( p > 0.05). The BW circuit also reduced readiness for IT SP (5.8 ± 2.2 vs. 7.5 ± 2.0 a.u., p < 0.05), with no significant changes in heart rate or rating of perceived exertion ( p > 0.05). These findings indicate that a BW circuit induces sufficient acute fatigue to impair subsequent interval running performance, regardless of sex. Coaches should consider exercise sequencing when integrating bodyweight circuits and high-intensity interval sessions within the same training day.